Late diagnosis of HIV: A lookback on cases in North Cumbria. (October 2019) - Khalifeh, B; Phillips, M; Barton, E
Late diagnosis of HIV remains a threat to personal and public health – both increasing the morbidity and mortality of the person and also increasing the chance of unknowingly transmitting HIV. Many HIV testing initiatives, including those of the British HIV Association (BHIVA), focus on levels of high prevalence (greater than 2:1000). However, late diagnosis can be an issue in areas of low prevalence – areas which can be less densely populated and in some cases classified as rural. In our rural catchment area, late diagnosis is an issue with 67% diagnosed late in 2015 (which is skewed by the single figure diagnoses). This lookback examined the number of missed opportunities for HIV diagnosis over a seven-year period and found that where diagnoses were made late in the context of a person having previously presented for care, unexplained weight loss, blood dyscrasias and lymphadenopathy were the most common presentations that could have triggered a HIV test.